Kar9p-independent Microtubule Capture at Bud6p Cortical Sites Primes Spindle Polarity before Bud Emergence in Saccharomyces cerevisiae - Segal, Marisa (The American Society for Cell Biology, 2002)
Spindle orientation is critical for accurate chromosomal segregation in eukaryotic cells. In the yeast Saccharomyces cerevisiae, orientation of the mitotic spindle is achieved by a program of microtubule–cortex interactions coupled to spindle morphogenesis. We previously implicated Bud6p in directing microtubule capture throughout this program. Herein, we have analyzed cells coexpressing GFP:Bud6 and GFP:Tub1 fusions, providing a kinetic view of Bud6p–microtubule interactions in live cells. Surprisingly, even during the G1 phase, microtubule capture at the recent division site and the incipient bud is dictated by Bud6p. These contacts are eliminated in bud6Δ cells but are proficient in kar9Δ cells. Thus, Bud6p cues microtubule capture, as soon as a new cell polarity axis is established independent of Kar9p. Bud6p increases the duration of interactions and promotes distinct modes of cortical association within the bud and neck regions. In particular, microtubule shrinkage and growth at the cortex rarely occur away from Bud6p sites. These are the interactions selectively impaired at the bud cortex in bud6Δ cells. Finally, interactions away from Bud6p sites within the bud differ from those occurring at the mother cell cortex, pointing to the existence of an independent factor controlling cortical contacts in mother cells after bud emergence.